2011
DOI: 10.1097/ss.0b013e31820e5e39
|View full text |Cite
|
Sign up to set email alerts
|

Improving Native Soil Athletic Fields With Intercept Drain Tile Installation and Subsequent Sand Topdressing Applications

Abstract: Intercept drain tile installation and subsequent sand topdressing applications can provide a built-up sand-based system. There are a number of different intercept drain tile spacing and sand layer depth recommendations. The objectives of this research were to determine the effects of intercept drain tile spacing on the surface runoff, soil water content, and surface shear strength of a compacted sandy loam with sand topdressing. A single factor, RCBD field study in East Lansing, Michigan, was seeded May 29, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…These findings suggest that recommendations for sand root‐zone selection, whether it be those provided by the USGA (28), ASTM (1,2), or Henderson et al (13), should be taken into consideration when selecting a cost‐effective sand topdressing material. Similar to research conducted by Kowalewski et al (15, 16), results also suggest that the benefits of sand topdressing increase when applications are repeated annually.…”
Section: Suggestions For Field Managerssupporting
confidence: 86%
See 2 more Smart Citations
“…These findings suggest that recommendations for sand root‐zone selection, whether it be those provided by the USGA (28), ASTM (1,2), or Henderson et al (13), should be taken into consideration when selecting a cost‐effective sand topdressing material. Similar to research conducted by Kowalewski et al (15, 16), results also suggest that the benefits of sand topdressing increase when applications are repeated annually.…”
Section: Suggestions For Field Managerssupporting
confidence: 86%
“…For instance, in 2008 when this research was initiated, in the lower peninsula of Michigan, prices for topdressing material were $10 per 1,000 kg for CPG and NPSD sand, $25 per 1,000 kg for USGA sand, and $30 per 1,000 kg for USGAF sand (prices based on communication with the local supplier J. W. Surge, Muskegon, MI, and do not include the cost of labor and transportation). According to these prices, if a field manager intended to apply a cumulative topdressing depth of 4.8 cm to a standard high school athletic field (5,351 m 2 ) for athletic field renovation (15), they would be spending approximately $4,195 for CPG and NPSD sand, $10,488 for USGA sand, $12,586 for USGAF sand. These particular sands were selected for this research because of their commercial availability for engineering and construction (CPG), golf course topdressing (NPSD and USGA), and athletic field construction (USGA and USGAF) throughout the state of Michigan.…”
Section: Topdressing and Simulated Trafficmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, research data that could lead to reliable recommendations for these questions are lacking. In temperate climates where the predominant turfgrasses are cool‐season species, Kowalewski, Crum, Rogers, and Dunne (2011, 2015) suggested that a 5‐cm cap of well‐graded sand combined with regularly spaced sub‐cap drainage lines would provide an acceptable surface for multipurpose sports fields that have become prone to muddy playing surfaces. Less has been done to investigate sand‐capping sports fields in subtropical climates where the predominant turfgrasses are warm‐season species such as bermudagrass (Miller, 2008).…”
Section: Introductionmentioning
confidence: 99%